Comparative Phytotoxicity Assays of the Herbicide Alloxydim and Its Main Identified Photoproduct in Cereal and Broadleaves Crops. Issue 2 (June 2015) - Sandín-España, Pilar; Sevilla-Morán, Beatriz; Villarroya-Ferruz, Mercedes; Alonso-Prados, José L.; Santín-Montanyá, M. Inés
Abstract : When herbicides are sprayed in the field, a proportion of the herbicide falls onto leaves and soil surfaces, where it can be exposed to sunlight, generating photoproducts that can be more toxic and/or persistent than the parent substance and affect human health and the environment. The aim of this study was to identify the photoproducts of the herbicide alloxydim in leaf and soil model systems and to perform phytotoxicity studies. Alloxydim was rapidly photodegraded in systems simulating plant cuticles and soil surfaces, with half-lives ranging from 1 to 30 min. The main by-product, identified by LC-Qtof-MS as deallyoxylated alloxydim, was more stable than the active substance. The EC50 values on root lengths of different varieties of wheat plants and one grass weed ranged from 0.38 to 0.50 mg L −1 for alloxydim. In contrast, the EC50 values for deallyoxylated alloxydim ranged from 94 to 600 mg L −1 in the same species and in crops where the herbicide was applied. Special attention should be given to alloxydim degradation products because of the rapid degradation of this herbicide. Comparative bioassay studies between alloxydim and its photostable by-product showed that the by-product presents low phytotoxicity, whereas alloxydim can cause injury to neighboring and succeeding cereal crops.